Metabolic Risk Factors with Stroke Among Indonesians - Sari, Indah Purnama; Nissa, Eldha An (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Stroke is one of the leading causes of death. It is not only in the world but also in Indonesia. Various factors that trigger the incidence of stroke are known as metabolic risk factors. This study aims to determine the risk of stroke caused by one or more metabolic risk factors. This study used a retrospective cohort design from secondary data from the 2007 and 2014 Indonesia Family Life Survey (IFLS). The population was the population aged 15 years and over. The sample was the population who did not experience a stroke in 2007 as many as 7,707 people. The sampling technique used was multistage random sampling. The results showed that as much as 1.8% of Indonesia’s population aged at least 15 years had a stroke. People with three metabolic risk factors had a 39.9 times higher risk of having a stroke than people without metabolic risk factors (95% CI: 29.3-54.4) after controlling for age, sex, and physical activity. Hypertension was a metabolic risk factor with the greatest risk for having a stroke. Therefore, preventive practices such as controlling and monitoring blood pressure, blood glucose levels and body weight can be carried out through regulating food consumption and engaging in regular physical activity.